Kontribusi Metode Diskusi dalam Mewujudkan Kompetensi Berfikir Kreatif Siswa MA Al-Hamidiyah Sen-Asen Konang Bangkalan - Yasin, Kholil (Pendidikan Agama Islam, 2018)
The discussion method is a method that can be used in learning activities, the discussion methodemphasizes the students' reasoning ability in studying the theories conveyed in the classroom. Thismethod can be used for many subjects because it is easy to apply and does not require complicatedpreparation and equipment. The discussion also became a good method for Al-Hamidiyah Madrasahstudents, although not entirely. By using the discussion method, the students creative thinkingcompetence are stimulated for developing progressively so that they have increased in along with thetimes, and can be said to be more better than before. The discussion method provides many positivecontributions in realizing students' creative thinking competencies. It can be seen from the increasingnumber of their creations in writing that published on wall magazine, bulletins and other forms ofcreative expressions, also can be seen from the increasing number of students who have alreadyfulfilled the criteria of creativity. The discussion method is also expected to be able to contribute notonly to how students develop their thinking potential in school but also in the social environment ofthe community